A Qualitative Study of Mindfulness Among Veterans With Posttraumatic Stress Disorder: Practices Differentially Affect Symptoms, Aspects of Well-Being, and Potential Mechanisms of Action - Dana Dharmakaya Colgan MA, MS, CYI-500; Helané Wahbeh ND; Mollie Pleet MA; Kristen Besler MA; Michael Christopher PhD (SAGE Publishing, 2017)
This qualitative study explored and compared the subjective experiences of 102 veterans with posttraumatic stress disorder (PTSD) who were randomly assigned to 1 of 4 arms: ( a ) body scan, ( b ) mindful breathing, ( c ) slow breathing, or ( d ) sitting quietly. Qualitative data were obtained via semistructured interviews following the intervention and analyzed using conventional content analysis. The percentage of participants within each intervention who endorsed a specific theme was calculated. Two-proportion z tests were then calculated to determine if the differences among themes endorsed in specific groups were statistically significant. Six core themes emerged from analysis of participant responses across the 4 groups: ( a ) enhanced present moment awareness, ( b ) increased nonreactivity, ( c ) increased nonjudgmental acceptance, ( d ) decreased physiological arousal and stress reactivity, ( e ) increased active coping skills, and ( f ) greater relaxation. More participants in the mindfulness intervention groups reported improvement in PTSD symptoms when compared to participants in non-mindfulness groups. Different types of intervention targeted different symptoms and aspects of well-being. Furthermore, type of intervention may have also differentially targeted potential mechanisms of action. This article highlights the importance of employing both quantitative and qualitative research methods when investigating the dynamic process of mindfulness and may inform how practices can be tailored to the needs of the veteran with PTSD.